Spatial analysis and hybrid machine learning prediction of forest fire susceptibility: a longitudinal appraisal synergy with physiographic division - Netrananda Sahu; Pritiranjan Das; Prince Gupta; Suraj Kumar Mallick; Rajiv Pandey; Xiaojun Wang; Manish Kumar; Ayush Varun; Ravi Kesharwani; Anil Kumar (Advances in Space Research, 2026)

Climate change impacts on vegetation dynamics and transhumant pastoralism in the Western Himalayas - Netrananda Sahu; Ravi Kesharwani; Yogeshwar Singh Rathore; Anil Kumar; Ayush Varun; Martand Mani Mishra; Pritiranjan Das; Basanta K. Das; Suraj Kumar Mallick (Environmental Monitoring and Assessment, 2026)

Role of urban green space structure and configuration in regulating land surface temperature in NCT Delhi using explainable artificial intelligence - Manish Kumar; Sourav Bhadwal; Netrananda Sahu (Urban Climate, 2026)

Spatiotemporal dynamics of rice cultivation in India - Netrananda Sahu; Ravi Kesharwani; Pritiranjan Das; Anil Kumar; Ayush Varun; Atul Saini; Suraj Kumar Mallick; Martand Mani Mishra (Tropical Ecology, 2025)

Application of geo-spatial and geo-statistical techniques in site suitability analysis for potential urban built-up area development - Somnath Rudra; Pritiranjan Das; Suraj Kumar Mallick; Biswajit Maity; Netrananda Sahu; Ulfat Khan (Environment, Development and Sustainability, 2025)

A bibliometric analysis for Indian summer monsoon variability - Netrananda Sahu; Pritiranjan Das; Satyaban B. Ratna; Atul Saini; Suraj Kumar Mallick; Anil Kumar; Mrutyunjay Mohapatra (Spatial Information Research, 2024)

Impact of urban growth in Delhi and It's Peri-urban environment on urban heat exposure - Suraj Kumar Mallick; Netrananda Sahu; Pritiranjan Das; Biswajit Maity; Ayush Varun; Anil Kumar; Ravi Keswarwani; Atul Saini; Somnath Rudra (Urban Climate, 2024)

Application of ensemble fuzzy weights of evidence-support vector machine (Fuzzy WofE-SVM) for urban flood modeling and coupled risk (CR) index for ward prioritization in NCT Delhi, India - Syed Irtiza Majid; Manish Kumar; Netrananda Sahu; Pankaj Kumar; Dinesh Kumar Tripathi (Environment, Development and Sustainability, 2024)

Geochemical evaluation and environmental risk assessment of heavy metals: A case study from Ireland using Tellus stream sediment data (2011–2017) - Pragya Pandit; Atul Saini; Netrananda Sahu; Rohit Mehra (Groundwater for Sustainable Development, 2023)

Rapid eco-physical impact assessment of tropical cyclones using geospatial technology: a case from severe cyclonic storms Amphan - Manoranjan Mishra; Dipika Kar; Manasi Debnath; Netrananda Sahu; Shreerup Goswami (Natural Hazards, 2022)

Decoding trend of Indian summer monsoon rainfall using multimethod approach - Atul Saini; Netrananda Sahu (Stochastic Environmental Research and Risk Assessment, 2021)

Probabilistic seasonal streamflow forecasts of the Citarum River, Indonesia, based on general circulation models - Netrananda Sahu; Andrew W. Robertson; Rizaldi Boer; Swadhin Behera; David G. DeWitt; Kaoru Takara; Manish Kumar; R. B. Singh (Stochastic Environmental Research and Risk Assessment, 2017)

Spatiotemporal variability of Hokkaido's seasonal precipitation in recent decades and connection to water vapour flux - Weili Duan; Bin He; Netrananda Sahu; Pingping Luo; Daniel Nover; Maochuan Hu; Kaoru Takara (International Journal of Climatology, 2017)
Based on 169 stations, annual, seasonal and monthly precipitation trends for the northern Japanese island of Hokkaido were analysed for the period 1980–2011 using the Mann–Kendall test and geostatistical interpolation techniques. Possible association with water vapour flux was explored using ERA ‐Interim reanalysis data. Precipitation increased in Hokkaido over the study period at both the annual and seasonal scales. In general, the northwest had higher precipitation than the southeast in winter, autumn and on an interannual basis and precipitation tended to be concentrated in the southeast in both spring and summer. There was also more precipitation during warm times of the year. For example, precipitation occurred mainly during the summer, ranging from 233 to 751 mm and autumn, ranging from 218 to 724 mm, while precipitation was significantly less in winter and spring. Most stations with declining precipitation trends were located in areas with higher precipitation, such as the west in winter and autumn and the southeast fringe in summer and scattered across the areas with lower precipitation in spring. Increases in precipitation were mainly seen in February, May, June, July, September, November and December at more than 100 stations. Amongst these, almost all of the stations showed positive trends in May (168 stations) and July (165 stations). Finally, the changes of the water vapour transport and budget in whole‐layers between the period 1980–2011 possibly explained the spatiotemporal distribution of precipitation trends in Hokkaido.

El Niño Modoki connection to extremely-low streamflow of the Paranaíba River in Brazil - Netrananda Sahu; Swadhin K. Behera; J. V. Ratnam; Roberto Valmir Da Silva; Pradipta Parhi; Weili Duan; Kaoru Takara; R. B. Singh; Toshio Yamagata (Climate Dynamics, 2014)

IOD and ENSO impacts on the extreme stream-flows of Citarum river in Indonesia - Netrananda Sahu; Swadhin K. Behera; Yosuke Yamashiki; Kaoru Takara; Toshio Yamagata (Climate Dynamics, 2012)